Calix[4]arene‐Based Triple‐Stranded Metallohelicate in Water. Issue 1 (17th November 2020) - Morie, Masayuki; Sekiya, Ryo; Haino, Takeharu
Abstract: The title complex is a triple‐stranded metallohelicate organized by the self‐assembly of 5, 17‐difunctionalized calix[4]arenes and metal cations with octahedral coordination geometry. Due to hydrophilic triethylene glycol chains on the lower rim of the calix[4]arene, the metallohelicate can encapsulate cationic guests in water. NMR and UV‐vis titration experiments reveal that the metallohelicate captures a pyridinium guest with an alanine derivative to form a host‐guest complex with a host‐guest ratio of 1 : 1. CD spectroscopy confirms the bias of the P ‐ and M ‐helical sense of the metallohelicate by the captured guest. The metallohelicate captures two molecules of dicationic N, N' ‐dimethyl‐DABCO and monocationic N ‐methyl quinuclidine, exhibiting a positive allosteric effect. 1 H NMR titration experiments indicate that the bound guests are in close proximately to the aromatic rings of the ligands. Molecular mechanics calculations based on the UV‐vis and NMR observations suggest that the first guest preorganizes the conformation of the metallohelicate to facilitate access of the second guest to the cavity. Abstract : A water‐soluble metallohelicate was generated. The triethylene glycol chains on the lower rim of the calix[4]arene core rendered the metallohelicate hydrophilic. The metallohelicate captured two cationic guests in a positively cooperative fashion due to the preorganization of the conformation of the metallohelicate by the first guest, facilitating access of the second guest to the cavity.